2012
DOI: 10.1104/pp.112.209213
|View full text |Cite
|
Sign up to set email alerts
|

The Rubisco Small Subunit Is Involved in Tobamovirus Movement and Tm-22-Mediated Extreme Resistance      

Abstract: The multifunctional movement protein (MP) of Tomato mosaic tobamovirus (ToMV) is involved in viral cell-to-cell movement, symptom development, and resistance gene recognition. However, it remains to be elucidated how ToMV  MP plays such diverse roles in plants. Here, we show that ToMV  MP interacts with the Rubisco small subunit (RbCS) of Nicotiana benthamiana in vitro and in vivo. In susceptible N. benthamiana plants, silencing of NbRbCS enabled ToMV to induce necrosis in inoculated leaves, thus enhancing vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
90
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 68 publications
4
90
0
1
Order By: Relevance
“…Recently, NtRbCS was reported to be the host target of potyvirus P3 protein and Tobamovirus multifunctional movement protein for virion replication (Danci et al, 2009) and systemic movement (Zhao et al, 2013). Transiently expressed fluorescence was detected in Nicotiana benthamiana lines co-infiltrated with pABP1-YFP C and pRbCS-YFP N through a bimolecular fluorescence complementation (BiFC) assay (Supplemental Figure 9).…”
Section: Auxin Binding Protein 1 Reinforces Resistance To Sugarcane Mmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, NtRbCS was reported to be the host target of potyvirus P3 protein and Tobamovirus multifunctional movement protein for virion replication (Danci et al, 2009) and systemic movement (Zhao et al, 2013). Transiently expressed fluorescence was detected in Nicotiana benthamiana lines co-infiltrated with pABP1-YFP C and pRbCS-YFP N through a bimolecular fluorescence complementation (BiFC) assay (Supplemental Figure 9).…”
Section: Auxin Binding Protein 1 Reinforces Resistance To Sugarcane Mmentioning
confidence: 98%
“…ZmABP1 expression is greatly stimulated by SCMV infection in resistant genotypes, reinforcing resistance to viruses that escaped from the Scmv1 barrier at later stages. As a consequence, ZmRbCS would neither be available for SCMV genome amplification nor utilized for potyvirus long-distance movements (Danci et al, 2009;Zhao et al, 2013). Scmv2 also confers resistance to other potyviruses, such as Maize dwarf mosaic virus and Wheat streak mosaic virus (L€ ubberstedt et al, 2006).…”
Section: Auxin Binding Protein 1 Reinforces Resistance To Sugarcane Mmentioning
confidence: 99%
“…In these screens Rubisco small subunit (RbCS) was identified as interacting with ToMV movement protein and SGT1 as interacting with Tm-22, in addition MP-Interacting Protein 1 (MIP1), a group of type I J-domain proteins was found to interact with both ToMV movement protein and Tm-22. By using VIGS and other in vitro and in vivo functional analysis in N. benthamiana, it was shown that MIP1s are required for both virus infection and plant immunity [144]. Furthermore, transgenic N. benthamiana plants expressing Tm-22, provides extreme resistance to ToMV, and VIGS mediated silencing of NbRbCS compromised Tm-22-dependent resistance, suggesting that RbCS of N. benthamiana plays an important role in ToMV movement and plant antiviral defenses [145].…”
Section: Signaling Components Acting Downstream Of Tomato Resistance mentioning
confidence: 99%
“…To identify the tomato proteins that interact with ToMV movement protein or Tm-22-LRR yeast two-hybrid screens were performed and tomato cDNA library was screened, by using ToMV movement protein and Tm-22-LRR as respective baits [144]. In these screens Rubisco small subunit (RbCS) was identified as interacting with ToMV movement protein and SGT1 as interacting with Tm-22, in addition MP-Interacting Protein 1 (MIP1), a group of type I J-domain proteins was found to interact with both ToMV movement protein and Tm-22.…”
Section: Signaling Components Acting Downstream Of Tomato Resistance mentioning
confidence: 99%
See 1 more Smart Citation